2020
DOI: 10.1590/s1808-185120201901220734
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Profile and Outcomes in Postoperative Neuromuscular Escoliosis

Abstract: Objective To outline the epidemiological profile and identify the hospital outcomes of patients submitted to neuromuscular scoliosis correction surgery. Methods This was a descriptive study that included 50 patients hospitalized following surgery for neuromuscular scoliosis in a tertiary-level hospital in São Paulo from January 2017 to July 2017. The variables were collected retrospectively from the patients’ medical records: age, sex, main diagnosis, length of hospital stay, duration of surgery, hospital c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Another fact that impacts the length of hospital stay, and consequently, hospital outcomes is immobility. 7,28 Therefore, defining and managing mobility goals is essential for monitoring results and their impacts on hospital outcomes. In this study, greater achievement of postoperative mobility goals was observed after the protocol, with an emphasis on early mobilization (p=0.001), elevation of the head of the bed to 60° on the 1 st PO day (p<0.005), and transfer/walking training on the 3 rd PO day (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another fact that impacts the length of hospital stay, and consequently, hospital outcomes is immobility. 7,28 Therefore, defining and managing mobility goals is essential for monitoring results and their impacts on hospital outcomes. In this study, greater achievement of postoperative mobility goals was observed after the protocol, with an emphasis on early mobilization (p=0.001), elevation of the head of the bed to 60° on the 1 st PO day (p<0.005), and transfer/walking training on the 3 rd PO day (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that 94% of patients with neuromuscular scoliosis had some type of mild complication, such as constipation, in the immediate postoperative period, while a small proportion had more severe complications, with the development of systemic inflammatory response syndrome in 16% of patients, and surgical site infection in 12%. 7 The postsurgical complications most frequently reported in the literature are acute respiratory distress syndrome, pneumonia, venous disorders such as thrombosis, gastrointestinal complications, surgical wound infection and dehiscence, pseudarthrosis and exacerbation of convulsive syndromes. Secondary complications are mostly related to reduced mobility in the postoperative period, and range from soft tissue injuries and decreased levels of physical fitness and bone/muscle mass, to impaired ventilatory function due to the high degree of curvature of the previous spinal deformity.…”
Section: Introductionmentioning
confidence: 99%
“…5 Surgical treatment is indicated in the presence of an increase in deformity and aims to correct the deformity, improve respiratory function, improve functional activity and patient care. 6,7 The surgical treatment is more complex than surgical treatment for idiopathic scoliosis, and arthrodesis with spinal fixation is more extensive, requiring inclusion of the pelvis in many patients. Postoperative complications occur more frequently compared to correction of other types of spinal deformity.…”
Section: Introductionmentioning
confidence: 99%